The Met Office Unified Model Global Atmosphere 3.0/3.1 and JULES Global Land 3.0/3.1 configurations - Walters, D. N.; Best, M. J.; Bushell, A. C.; Copsey, D.; Edwards, J. M.; Falloon, P. D.; Harris, C. M.; Lock, A. P.; Manners, J. C.; Morcrette, C. J.; Roberts, M. J.; Stratton, R. A.; et al. (Geoscientific Model Development, 2011)
We describe Global Atmosphere 3.0 (GA3.0): a configuration of the Met Office Unified Model (MetUM) developed for use across climate research and weather prediction activities. GA3.0 has been formulated by converging the development paths of the Met Office's weather and climate global atmospheric model components such that wherever possible, atmospheric processes are modelled or parametrized seamlessly across spatial resolutions and timescales. This unified development process will provide the Met Office and its collaborators with regular releases of a configuration that has been evaluated, and can hence be applied, over a variety of modelling régimes. We also describe Global Land 3.0 (GL3.0): a configuration of the JULES community land surface model developed for use with GA3.0. This paper provides a comprehensive technical and scientific description of the GA3.0 and GL3.0 (and related GA3.1 and GL3.1) configurations and presents the results of some initial evaluations of their performance in various applications. It is to be the first in a series of papers describing each subsequent Global Atmosphere release; this will provide a single source of reference for established users and developers as well as researchers requiring access to a current, but trusted, global MetUM setup.